2006
DOI: 10.1007/s11239-006-8322-2
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume in gestational diabetes

Abstract: There is a need for further research focusing on the platelet function in the observation and treatment of gestational diabetes, which can pose the risk of developing Type 2 diabetes for the mother and has negative consequences for the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 19 publications
3
35
1
1
Order By: Relevance
“…Conflicting results were obtained about the platelet count in patients with GDM in some studies. A significant difference in platelet count was not observed between the studies of Bozkurt et al (13) and Erdogan et al (10). The platelet count was found significantly lower than the control in the study of Erikçi et al (14).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Conflicting results were obtained about the platelet count in patients with GDM in some studies. A significant difference in platelet count was not observed between the studies of Bozkurt et al (13) and Erdogan et al (10). The platelet count was found significantly lower than the control in the study of Erikçi et al (14).…”
Section: Discussionmentioning
confidence: 71%
“…Significant changes have not been found in neither PLR nor NLR in the study of Sargin et al (18). A number of studies have revealed the increase of MPV in patients with the GDM (13,14,19) however this issue is also contradictory. Sahbaz et al (11) have conducted a retrospective study on 59 GDM patients and the MPV level was higher than the level of healthy group but Erdogan et al (10) have not found a significant change in their study in patients with GDM.…”
Section: Discussionmentioning
confidence: 91%
“…There was also no correlation between MPV and fasting blood glucose levels of pregnants with GDM. Previously two studies detected higher MPV in patients with GDM when compared to the control group, [7,8] but they did not check the presence of correlation between MPV and glucose levels. Other studies in patients with type 2 DM detected statistically significantly higher MPV in diabetic group when compared to nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 86%
“…[4] Large platelets are more active than smaller platelets and produce more prothrombotic factors and this indicates that changes in the platelet count and MPV reflect the state of thrombogenesis. [4] Mean platelet volume of patients with type 2 DM are higher than controls [5,6] and patients with GDM also have higher MPV, [7,8] yet other studies present contradictory results. [9] In this study we measured MPV in patients with GDM and compared it to nondiabetics and tried to determine the correlation of MPV with postprandial plasma glucose in patients diagnosed with GDM.…”
mentioning
confidence: 99%
“…Bizim çalışmamızda gestasyonel diyabet grubunda MPV ve HbA1c düzeyi anlamlı olarak yüksek tespit edildi. Bozkurt ve arkadaşları (14) gestasyonel diyabetik hastalarda kontrol grubuna göre yüksek MPV düzeyleri ve düşük trombosit sayısı ile birliktelik gösterdiğini, trombosit sayısının düşüklüğünün diyabetik hastalarda trombosit ömrünün daha kısa olması ile açıklamışlardır. Bizim çalışmamızda MPV düzeyleri iki grup arasında anlamlı farklı çıkarken, trombosit sayıları iki grupta benzer olarak bulundu.…”
Section: Introductionunclassified